MRJP1-containing glycoproteins isolated from honey, a novel antibacterial drug candidate with broad spectrum activity against multi-drug resistant clinical isolates - Brudzynski, Katrina; Sjaarda, Calvin; Lannigan, Robert (Frontiers in Microbiology, 2015)
The emergence of extended- spectrum β-lactamase (ESBL) is the underlying cause of growing antibiotic resistance among Gram-negative bacteria to β-lactam antibiotics. We recently reported the discovery of honey glycoproteins (glps) that exhibited a rapid, concentration-dependent antibacterial activity against both Gram-positive Bacillus subtilis and Gram-negative Escherichia coli that resembled action of cell wall-active β-lactam drugs. Glps showed sequence identity with the Major Royal Jelly Protein 1 (MRJP1) precursor that harbors three antimicrobial peptides: Jelleins 1, 2 and 4. Here, we used semi-quantitative radial diffusion assay and broth microdilution assay to evaluate susceptibility of a number of multi-drug resistant (MDR) clinical isolates to the MRJP1-contaning honey glycoproteins. The MDR bacterial strains comprised 3 MRSA, 4 Pseudomonas aeruginosa, 2 Klebsiella pneumoniae, 2 VRE and 5 Extended-spectrum beta-lactamase (ESBL) identified as 1 Proteus mirabilis, 3 Escherichia coli and 1 Escherichia coli NDM. Their resistance to different classes of antibiotics was confirmed using automated system Vitek 2. MDR isolates differred in their susceptibility to glps with MIC90 values ranging from 4.8μg/ml against B. subtilis to 14.4μg/ml against ESBL K. pneumoniae, Klebsiella spp ESBL and E. coli and up to 33μg/ml against highly resistant strains of P. aeruginosa. Glps isolated from different honeys showed a similar ability to overcome bacterial resistance to β-lactams suggesting that (a) their mode of action is distinct from other classes of β-lactams and that (b) the common glps structure was the lead structure responsible for the activity. The results of the current study together with our previous evidence of a rapid bactericidal activity of glps demonstrate that glps possess suitable characteristics to be considered a novel antibacterial drug candidate.